Whole-Genome Sequencing of the Giant Devil Catfish, Bagarius yarrelli. (5th July 2019) - Jiang, Wansheng; Lv, Yunyun; Cheng, Le; Yang, Kunfeng; Bian, Chao; Wang, Xiaoai; Li, Yanping; Pan, Xiaofu; You, Xinxin; Zhang, Yuanwei; Yang, Jinlong; Li, Jia; et al.
Abstract: As one economically important fish in the southeastern Himalayas, the giant devil catfish ( Bagarius yarrelli ) has been known for its extraordinarily large body size. It can grow up to 2 m, whereas the non- Bagarius sisorids only reach 10–30 cm. Another outstanding characteristic of Bagarius species is the salmonids-like reddish flesh color. Both body size and flesh color are interesting questions in science and also valuable features in aquaculture that worth of deep investigations. Bagarius species therefore are ideal materials for studying body size evolution and color depositions in fish muscles, and also potential organisms for extensive utilization in Asian freshwater aquaculture. In a combination of Illumina and PacBio sequencing technologies, we de novo assembled a 571-Mb genome for the giant devil catfish from a total of 153.4-Gb clean reads. The scaffold and contig N50 values are 3.1 and 1.6 Mb, respectively. This genome assembly was evaluated with 93.4% of Benchmarking Universal Single-Copy Orthologs completeness, 98% of transcripts coverage, and highly homologous with a chromosome-level-based genome of channel catfish ( Ictalurus punctatus ). We detected that 35.26% of the genome assembly is composed of repetitive elements. Employing homology, de novo, and transcriptome-based annotations, we annotated a total of 19, 027 protein-coding genes for further use. In summary, we generated the first high-quality genome assembly of the giant devil catfish, which provides an important genomic resource for its future studies such as the body size and flesh color issues, and also for facilitating the conservation and utilization of this valuable catfish.